Gensko spremenjene mlečnokislinske bakterije kot dostavni sistemi za biološka zdravila - Berlec, Aleš (Farmacevtski vestnik, 2008)
Lactic acid bacteria have been a part of human diet for centuries and their safety is therefore generally recognised. Apart from that, the techniques thatenable recombinant protein expression in lactic acid bacteria have recently developed. This is why lactic acid bacteria could serve as a cheap and efficient delivery system for recombinant protein delivery to body mucosa,especially in gastrointestinal tract. Systems for antigen (vaccine) delivery, delivery of proteins with physiological function and for DNA delivery are under development and in animal testing. The delivery of interleukin IL-10 in inflammatory bowel disease is the most promising and was successfully tested in phase I human clinical trial. Before the widespread use, questions regarding safety of genetic material introduction will have to be answered, since these are genetically modified organisms, which are not well accepted by the general public.
Keywords: dostava zdravilnih učinkovin; gensko spremenjeni organizmi; mlečnokislinske bakterije; rekombinantni proteini